Aplicações computacionais na metalurgia - Araujo, Larissa Garcia Sansoni (Universidade Federal de São Carlos, 2023)
Currently, computer simulations and computational calculations have been prominent in virtually every engineering field. This is attributed to the development of new products and the pursuit of cost, time, and resource reduction in trials and experimental tests. In metallurgy, computer simulations and computational calculations play a particularly significant role, owing to their capability to model complex processes of transformation and treatment of metallic materials, enabling the prediction of how different variables affect the final properties of the materials. This not only expedites the development process but also provides an understanding of the relationships among the involved variables, as well as allowing the exploration of scenarios that would be conducted experimentally. Thus, the existence of a practical guide for software selection in metallurgy becomes interesting, based on a comprehensive survey of available tools at different stages of the process. In light of this, the aim of this work was to identify the functionalities of each software, thereby assisting professionals in choosing the most suitable tools for their needs, avoiding the waste of time and resources in attempts to find the most appropriate solutions through trial and error. It is worth noting here that computer simulations and calculations depend on a database with accurate information, as the quality of results obtained with any software is directly linked to the quality of the input data. To ensure the reliability of the results, it is essential for the parameters and properties used in the models to reflect the actual characteristics of the materials and processes being analyzed.
Computational applications in metallurgy
Keywords: Metalurgia; Simulação computacional; Metallurgy; Computer simulation; Software; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::INSTALACOES E EQUIPAMENTOS METALURGICOS